The role of patients, caregivers, and communities in Learning Health Systems: a narrative review - Giacomantonio, Rachel; Dunn, Susan; Rubenstein, Donna; Somerville, Mari; Hemming, Kristen; McLaughlin, Lauren; Finlay, Teresa; Wherton, Joseph (Frontiers in Health Services, 2025)
Learning Health Systems (LHSs) seek to continuously generate and apply evidence in clinical practice. Most Canadian LHS models emphasize engagement with patients, caregivers, and communities (herein contributors). Yet, there is limited guidance about how engagement works in these dynamic systems and how it may differ from engagement in other settings, for example patient-oriented research and quality improvement. This review examines engagement activities in existing and emerging LHSs for insights into the roles that contributors play in creating patient-oriented and equitable LHSs. A narrative review was conducted using the PerSPEcTiF framework. Search terms were identified for three domains: contributors, LHSs operating in direct patient care settings, and active engagement. Four databases (PubMed-MEDLINE, CINAHL, PsycINFO, Embase) were searched in December 2022. Articles were screened using a domain-based rubric and sampled for richness. Data were extracted including who was engaged, when, where, and how. Engagement activities were coded inductively, then deductively using the International Association for Public Participation (IAP2) Spectrum of Public Participation. An advisory group, including a Patient Partner, provided input at several stages in the project. Thirty-six articles describing engagement in 30 LHSs were included. In all, 192 engagement activities were coded to create a taxonomy of engagement; 139 activities were also coded to the IAP2 Spectrum. Contributors' influence over decision-making was often unclear or limited, with engagement frequently occurring after LHS implementation. However, LHSs also provided contributors with opportunities to engage in deliberative system design and effect change through distributed leadership. Ten contributor roles were synthesized, serving three functions: “System Shapers” (designing and defining LHSs), “Community and Capacity Builders” (expanding and supporting LHSs), and “Implementers” (hands-on efforts). This review provides an overview of engagement in LHSs, demonstrating how these practices can both build on and be constrained by engagement traditions in patient-oriented research and quality improvement. Findings offer a starting point for designing meaningful contributor roles and highlight opportunities to reimagine engagement practices by embedding contributors within systems and engaging communities beyond patient care settings.